Evolution, domestication and neo-domestication of the genus Vigna. (16th July 2014) - Tomooka, Norihiko; Naito, Ken; Kaga, Akito; Sakai, Hiroaki; Isemura, Takehisa; Ogiso-Tanaka, Eri; Iseki, Kohtaro; Takahashi, Yu
Abstract : In this paper, we discuss stress-adapted wild Vigna plants and several important Vigna crops. Seeds, young shoots and/or tubers of many wild Vigna species are edible and are eaten by people in some locations where they grow. We propose the concept of 'neo-domestication' of stress-adapted wild edible Vigna species. As the causative change of the mutation resulting in a domestication gene is usually 'loss-of-function' type, 'neo-domestication' could be achieved by conventional mutation breeding together with screening by TILLING. The 'neo-crops' could play an important role in areas unsuitable for growing other crops to increase world food production. We also propose that wild Vigna species can be 'new model plant species' for the genetic study of natural adaptation to stresses (e.g. salt, acid, alkali, drought, flood, pests and diseases). To facilitate this, the Vigna Genome Project has been initiated. In addition, sustainable cropping systems may be enhanced by analysis of the nitrogen-fixing systems of stress-adapted Vigna species. Stress-adapted symbiotic bacteria produce nodules on stress-adapted Vigna species. Therefore, analyses of the genetic diversity of symbiotic bacteria and the process of symbiosis under stress environments should be conducted.